The Power of Screenshot Evidence in Proving Cyber Crimes - Juliharto, Vira Auliya (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
This research analyzes the strength of screenshot evidence in proving cybercrime by combining a normative juridical approach with empirical analysis of investigative practices and court decisions. The findings indicate that screenshots hold significant probative value, although their validity strongly depends on digital authentication, data integrity, and forensic support. Screenshots cannot stand alone and require technical verification through metadata examination, hash value analysis, and digital reconstruction. The study also highlights that Indonesia lacks uniform standards for handling electronic evidence, which affects the quality of proof in court. The analysis demonstrates the urgency of updating national guidelines and improving the technical capacity of law enforcement to ensure the reliability of electronic evidence. Overall, this research emphasizes the importance of proper technical and normative procedures in ensuring the legal strength of screenshot evidence in cybercrime cases.